Rancang Bangun Aplikasi Koleksi Resep Makanan Berbasis Sistem Operasi iPhone - Jessica Wienadi; Yosua Setyawan Soekamto (Maranatha University Press, 2022)
Food is a necessity that is needed by anyone. One way to obtain food is to cook. Many people choose to cook their own food, even more so during the Covid-19 pandemic which caused cooking preferences to increase. One of the things used when cooking is recipes. Recipes need to be saved for easy reuse. Hence built a food recipe collection app that helps store recipes on mobile devices. The application is built on iOS. To find out the problems and needs in recipe saving, interviews were conducted, and problems were found regarding separated storing location and diverse storing format, limited search capabilities on current saving method, time-consuming input processes, and disturbing automatic-lock on device. Analysis of similar applications were also conducted and found shortcomings related to the flow and application interface. Based on these results, the application is designed with two main features, namely recipe storage and cooking mode. In recipe storage, users can add, change, and delete recipes. Once a recipe is saved, users can view a list of saved recipes, view recipes by category, and search for recipes by title. In cooking mode, users are given a checklist to prepare ingredients and then given a step-by-step. Application development uses the Swift programming language, with Swift User Interface to build the app's interface. Application data is stored locally using Core Data. Testing of application implementation results is carried out using alpha test and beta test. Alpha tests are performed using black-box test, to ensure the accuracy of inputs and outputs of various application functions. The beta test is done by conducting application trials and interviews with cooks to ensure application usability and to obtain feedbacks from users. Based on the test results, all functions in the application run as expected and this application helps users save food recipe collection.